EFFECT OF TRANSFORMATIONAL, TRANSACTIONAL AND AMBIDEXTROUS LEADERSHIP ON PUBLIC HEALTH EMPLOYEE SUSTAINABLE PERFORMANCE IN NIGERIA: THE ROLE OF GOVERNANCE QUALITY - Osuagwu Justine Ugochukwu (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The importance of employee well-being in healthcare is crucial because of the urgent and ongoing demands for the delivery of care and service to patients. The service level and treatment delivery are often inefficient, ineffective, and not patient-friendly due to high workloads, unforeseen tasks, emergencies, bad working circumstances, lack of managerial support, and inadequate equipment. These difficulties require comprehensive healthcare solutions that address all aspects of employee well-being. Nevertheless, there is a lack of research on how factors such as leadership styles and governance quality might improve employee sustainable performance in the healthcare sector. This study examined the correlation between transactional, and ambidextrous leadership styles and the sustainable performance of employees in healthcare units. The study also examined how governance quality influences the connection between leadership styles and the sustainable performance of employees. The main objective of this research was to provide a framework for healthcare leadership and employee sustainability in order to improve healthcare services for the population of Nigeria. The study employed a cross-sectional quantitative approach, gathering data using both online and in-person survey questionnaires. The study sample comprised medical physicians employed in the public healthcare sector of the southeastern states in Nigeria. A method of sampling called proportionate stratified random sampling was employed to select a subset of individuals from the intended population. The software program SPSS was utilized to do descriptive statistical analysis, while the SmartPLS software was employed to examine the correlations between the variables using structural equation modeling. We received a total of 117 responses that were usable. The results indicated a strong and favorable correlation between transactional, ambidextrous leadership styles, governance quality, and employee sustainable performance. The conditional path analysis indicated that there was no mediating effect of governance quality on the association between ambidextrous leadership styles and employee sustainable performance. The transactional leadership styles and employee sustainable performance is totally mediated by governance quality. The study was noteworthy because its findings aligned with the theories of leadership, governance excellence, and employee sustainable performance. The study has furnished empirical evidence to practitioners and policymakers in health and public sector organizations regarding the correlation between leadership styles, employee sustainable performance, and the role of governance quality as a mediator. The findings emphasized the necessary leadership behaviors required for managing healthcare institutions and achieving long-term employee engagement. Health managers can enhance their understanding of organizational leadership, employee well-being, and institutional quality dynamics by utilizing a framework that enables them to reevaluate their competencies and identify areas for improvement. Future researchers are advised to employ larger sample sizes and qualitative research approaches in order to generalize the findings of this study. It is imperative to extend the inclusion of other groups, such as administrative workers and technicians, as they play a crucial role in the functioning of the healthcare delivery system. Conducting research on the extensive private healthcare sector, despite the fact that their employees' sustainable performance is not as poor as that of the public healthcare sector is needed.